2019
DOI: 10.1039/c8nj04314k
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of gold nanoparticles with two aminoalcohol-based quinoxaline derivatives for targeting phosphoinositide 3-kinases (PI3Kα)

Abstract: Quinoxaline derivatives have attracted considerable attention due to their vast range of applications that includes electroluminescence and biomedicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…One study showed that GNPs were easily functionalized using 2,3-diethanolminoquinoxaline (DEQX) and 2-(2,3-dihydro- [1,4] oxazino [2,3- b] quinoxaline -4-yl) ethanol (OAQX). They used these conjugates to target cancer cells, because compounds with a quinoxaline motif can bind to phosphatidylinositol-4,5-bisphosphate 3-kinases (PI3Ks) and these enzymes are overexpressed in some types of neoplasms ( Araújo et al, 2019 ). Quinoxaline derivatives have also been used to functionalize silver and gadolinium-based nanoparticles and were shown to give excellent stability, while providing functional groups such as -NH 2 or -OH, which could serve for the binding of different ligands ( Morlieras et al, 2013 ; Neri et al, 2021 ).…”
Section: Functionalization Methodsmentioning
confidence: 99%
“…One study showed that GNPs were easily functionalized using 2,3-diethanolminoquinoxaline (DEQX) and 2-(2,3-dihydro- [1,4] oxazino [2,3- b] quinoxaline -4-yl) ethanol (OAQX). They used these conjugates to target cancer cells, because compounds with a quinoxaline motif can bind to phosphatidylinositol-4,5-bisphosphate 3-kinases (PI3Ks) and these enzymes are overexpressed in some types of neoplasms ( Araújo et al, 2019 ). Quinoxaline derivatives have also been used to functionalize silver and gadolinium-based nanoparticles and were shown to give excellent stability, while providing functional groups such as -NH 2 or -OH, which could serve for the binding of different ligands ( Morlieras et al, 2013 ; Neri et al, 2021 ).…”
Section: Functionalization Methodsmentioning
confidence: 99%
“…In the past few decades, design and characterisations of heterocyclic organic compounds have received considerable attention because of their pivotal role and wide application in different areas of life science . Particularly, nitrogen‐containing heterocyclic systems are known to exhibit excellent pharmacological activities .…”
Section: Introductionmentioning
confidence: 99%